STRATEGI BUPATI DAN WAKIL BUPATI DALAM PELAKSANAAN PROGRAM BUPATI BEKERJA DAN BERKANTOR DI KAMPUNG (BUJANG KAMPUNG) KABUPATEN SIAK TAHUN 2023 - Lestari, Niken Fujia; Zebua, Ben Hansel Notatema (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The regent working and having an office in the village (Bujang Kampung) program is an initiative of the Siak Regency Government to improve access and quality of health services in remote areas. This program offers free health services, including specialist doctors, but faces several challenges such as a lack of specialist doctors, limited implementation time, less effective outreach, and a budget that was not allocated well at the beginning of the year. This program has also received the attention of the Indonesian Ombudsman and is dealing with high rates of diseases such as Dengue Hemorrhagic Fever (DHF) and Acute Respiratory Infections (ARI). This study uses a descriptive qualitative method, with the determination of informants using purposive sampling techniques, with the theory of government strategy by Geoff Mulgan (2009) with indicators of purpose, environment, directions, actions, and learning. This study explains the strategy of the Regent and Deputy Regent in implementing the Regent Working and Having an Office in the Village (Bujang Kampung) of Siak Regency in 2023. The results of the study show that the Regent and Deputy Regent of Siak issued Regent Regulation No. 6 of 2024 concerning the Implementation of Public Services through the Bujang Kampung Program (Regents Working and Having Offices in Villages). Several strategies implemented include intensive communication between agencies, budget optimization through ORGANISASI PERANGKAT DAERAH (OPD) operational funds, and the launch of the